ACADEMIC WRITING: RELEVANT CONTENT FOR RUSSIA - Elina S. Chuikova (Высшее образование в России)
Abstract. Social and political changes bring the interest to academic writing into life, however, educational realia specify the content of academic writing that is relevant for Russia. Teaching predominantly non-academic students could be distinguished as the first factor that determines specific content in native tradition. The second factor deals with the structuring of the educational process: teaching academic writing is a two-staged process abroad while in Russia we miss one of the stages (generally the initial one). Practical teaching experience enables to single out an additional factor, i.e. a leading approach to teaching academic writing. In case with the genre-based approach, a number of genres of academic texts are on the focus. If one tends to a process-oriented writing, then some rhetorical elements could be included into the content. In the article the author specifies and systematizes both genres and rhetorical elements relevant for Russian educational needs. They overlap if we pay attention to sociocultural peculiarities of the genres and their rhetorical structure in English. Introduction of the sociocultural aspect reflects the needs of person oriented approach as it motivates students to academic writing learning.